ANALYSIS OF LATERAL FORCES ON A MULTI-STORIED FRAME STRUCTURE USING D-VALUE METHOD AND ITS COMPARISON WITH FINITE ELEMENT METHOD (Pakistan Journal of Science, 2022)
Multi-storied frame structures have always been in the lime-light as far as researchand theoretical development is concerned. The behavior of lateral forces on the structures is a specificarea on which considerable research has been done over the last few decades. Several experiences ofthe last century have brought the attention of the engineers to such forces which, at times, weresignificant enough to change the design criteria. In Pakistan, considerations for such lateral forces hadbeen made compulsory by the building control authorities across the country, and the same werewelcomed, after the catastrophic disaster of October 2005. However, the developmental research in thefield is still underway like in rest of the world. Most of the structural designers in Pakistan depend onComputer Aided Design software for analysis of lateral forces; however, significance of classicalmethods cannot be over-ruled. In this study, an attempt was made by studying the comparison betweenthe design results of a multi-storied moment resisting frame structure in Karachi using the D-valuemethod and ETABS software. There are several parameters on which the comparison could be based,but as the designers are mostly concerned about the design moments, the comparison is based upon thedifference between the moments caused on respective joints by the lateral forces only. D-value methodis not only a straightforward method but also may be considered to be the nearest compatible methodto the finite element method (ETABS), for the analysis of lateral forces on super-structures, as itsresults showed a variation of only 20% with that of the results from ETABS. It is recommended forpreferable use D-value method upon other methods of analysis when it comes to the scrutiny orverification of moments from the CAD software however, the difference between the comparativeresults may vary for type of structures other than the moment resisting frame structures.
Keywords: Frame Structures; Lateral Forces; D-value Method; ETABS; CAD Software